Metabolomics analysis on antifungal activities produced by Penicillium oxalicum T3.3 grown on different types of carbon sources - Salikin, Nurliyana (2015)
Anthracnose is a disease caused by a fungal Colletotrichum gleosporioides. It is a common disease to dragon fruit plant and has caused a great loss to this industry. This pathogenic fungus can cause damage to most parts of plants including roots, stems, leaves, flowers and fruits. One of the potential microorganisms that able to produce antimicrobial activity against this plant pathogen is the endophytic fungus. However, research carried out on metabolomics of cellular metabolites produced by endophytic Penicillium oxalicum against C. gleosporioides is very limited. Thus, this study was conducted with the aims to evaluate the antifungal activities produced by Penicillium oxalicum T3.3 against Colletotrichum gloeosporiodes by using different types of carbon sources in fermentation medium and to identify the possible compounds produced by this strain through metabolomics approach. Preliminary study on locally isolated; P. oxalicum T3.3 had shown a promising antagonism through antifungal secondary metabolites which suppressed the growth of C. gloeosporioides. Disc diffusion test was conducted in order to determine the inhibition zone on the growth of C. gloeosproides. Among the six carbon sources tested, glucose exhibited the highest percent inhibition of radial growth (PIRG) of 75% and producing inhibition zone ranges from 4 to 7 mm. The minimum inhibition concentration (MIC) and minimum fungicidal concentration (MFC) of the glucose crude extract was the highest with 78 μg/mL and 2500 μg/mL, respectively. Meanwhile, starch and xylitol crude extracts gave the lowest MIC value of 1250 μg/mL and no MFC can be recorded. The compounds were extracted with ethyl acetate and 1H NMR analysis was carried out to identify candidate compounds that had been produced. Metabolomics studies were conducted by analyzing the spectrum using SIMCA P+, Principal Component Analysis (PCA) and Partial Least Square (PLS) multivariate statistical method. The conducted metabolomics study showed that sugar crude extracts (glucose, sucrose and maltose) tend to produce more threonine, 2-heptanone, lactate, valine, butyrate, O-phosphoserine. Meanwhile complex sugar substrates (xylitol, starch and Undaria pinnatifida) produced more acetic acid, methionine and leucine. From this analysis, different metabolites produced by P. oxalicum T3.3 were clustered according to the carbon sources used. This research demonstrates the potential of using a combination of 1H NMR spectroscopy and multivariate data analyses in differentiating the effect of carbon sources used based on the identification of possible metabolites contributing to their differences.